Comparative Analysis of Financial Distress Models in Predicting Bankruptcy during Covid-19 Pandemic - Dede Hertina; Farida Wulan Dari (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
This study aims to determine whether there is a difference between the financial distress models in predicting bankruptcy, and the most accurate financial distress models bankruptcy in construction and building companies listed on Indonesia’s Stock Exchange for the 2020-2021 period. The financial distress models used in this research are Springate, Taffler, and Zmijewski. The research population consisted of 18 companies and the sample was taken as many as 16 companies using purposive sampling method. The data research was collected from the company’s financial statement. This research uses a descriptive comparative method by conducting the Kruskal Wallis test to determine the difference between the Springate, Taffler, and Zmijewski. The results showed that there is a significant difference between the financial distress models in predicting bankruptcy predictions for the construction and building companies listed on Indonesia’s Stock Exchange for the 2020-2021 period. The most accurate model in bankruptcy prediction is the Taffler model with an accuracy rate of 100% and the error rate of 0%. Zmijewski has 81,25% of accuracy rate and 18,75% of error. Then the lowest accurate model in bankruptcy prediction is the Springate model with 12,50% of accuracy and 87,50% of error rate.